Environmental radiation in the Cusco-Machu Picchu route - Manosalva Bacigalupo, Julio (2013)
The global average background dose for a human being is about 2.4 millisievert (mSv) per year. This exposure is produced mainly by cosmic radiation and radioactive materials that are naturally in the environment and are the reason why the level of natural radiation of the background varies from one zone to another in some areas and that this level is significantly higher than the average [3]. Such areas include Ramsar in Iran, Guarapari in Brazil, Kerala in India, the northern Flinders Ranges in Australia and Yangjiang in China. In order to know the background radiation in our country, and their possible impacts on living things continue along these lines, the present study was conducted environmental ionizing radiation measurements along routes linking Cuzco to Machu Picchu. In these locations 10 measurements were made at random locations away at least 6 meters of buildings to a meter from the ground with a Geiger-Müller detector Portable Gamma- Scout brand, calibrated (Fachhochschuler Mannheim) at equivalent doses (nSv / h). Calca area is the highest reading with 478 nano Sv / h, 470 followed by Ollantaytambo, Pisac high 440, 396 Poroy, Calca 388 Machupichu 343, 342 Pisac, Aguas Calientes 298 and others totaling from 29 localities.